Efficiency improvements with low heat rejection concepts applied to diesel low temperature combustion. (August 2016) - Penny, Michael A; Jacobs, Timothy J
There is a strong motivation to decrease the production and release of harmful substances such as oxides of nitrogen (NOX ) and particulate matter from internal combustion engines. Simultaneously, there are on-going efforts to increase fuel efficiency to curb usage of natural resources and emission of carbon. In general, improvements in one of these areas come at the cost of the other; however, the results of a previous computational study have indicated that emissions can be decreased while simultaneously increasing efficiency through the application of low heat rejection techniques to low temperature combustion. The goal of this study is to experimentally confirm these findings using a light-duty, multi-cylinder diesel engine. Low temperature combustion is realized through high levels of exhaust gas recirculation and retarded injection timings while different degrees of low heat rejection are achieved by means of higher coolant temperatures which should serve to decrease the temperature gradients across the cylinder walls. By applying low heat rejection techniques to diesel low temperature combustion operation, the undesirable side effects of low temperature combustion such as lower combustion and energy conversion efficiencies were found to be mitigated. Specifically, the emissions of carbon monoxide and unburned hydrocarbons were reduced and the loss in fuel conversion efficiency was also diminished. NOX and smoke (an indicator of particulate matter) emissions did increase but they remained at acceptably low levels and below those of conventional combustion. While the full potential of improvements in low temperature combustion was not explored, these results point to the viability of further research into low heat rejection–low temperature combustion concepts.